The Influence of Ethical Leadership, Teacher Capacity Building, and School Culture on the Performance of Madrasah Tsanawiyah Teachers - Ananda, Rusydi; Sukoco, Sugeng; Khairuddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
This research is based on problems related to teacher performance seen from the perspective of the influence of ethical leadership, teacher capacity building, and school culture. The research objective is to describe: and school culture on teacher performance. (1) ethical leadership has a significant effect on school culture, (2) teacher capacity building has a significant effect on school culture (3) ethical leadership has a significant effect on teacher performance, (4) teacher capacity building leadership has a significant effect on teacher performance, ( 5) school culture has a significant effect on teacher performance, (6) ethical leadership has a significant effect on teacher performance through school culture (7) teacher capacity building has a significant effect on teacher performance through school culture and (8) the simultaneous influence of ethical leadership, teacher capacity building on teacher performance. The research method used is quantitative research using an expostfacto approach. The research population was 757 madrasah tsanawiyah teachers in Batubara Regency with a selected sample of 238 spread across 53 madrasas. The data collection instrument is a questionnaire designed with a Likert scale. The research hypothesis was tested using path analyst data analysis techniques. The research results show: (1) ethical leadership has a significant effect on school culture by 45.00%, (2) teacher capacity building has a significant effect on school culture by 66.90%, (3) ethical leadership has a significant effect on teacher performance of 33.00%, (4) teacher capacity building has a significant effect on teacher performance of 59.80%, (5) school culture has a significant effect on teacher performance of 37.50%, (6) ethical leadership has a significant effect on teacher performance through school culture was 61.40%, (7) teacher capacity building had a significant effect on teacher performance through school culture by 65.60%, and (8) ethical leadership, teacher capacity building, school culture simultaneously had an effect on performance Teacher. The findings of this research have the implication that efforts to improve teacher school culture can be done by increasing teacher capacity building among Madrasah Tsanawiyah teachers.